Labour supply: a review of alternative approaches - Richard Blundell; Thomas MaCurdy (Institute for Fiscal Studies (IFS), 1998)
This chapter surveys existing approaches to modeling labor supply and identifies important gaps in the literature that could be addressed in future research. The discussion begins with a look at recent policy reforms and labor market facts that motivate the study of labor supply. The analysis then presents a unifying framework that allows alternative empirical formulations of the labor supply model to be compared and their resulting elasticities to be interpreted. This is followed by critical reviews of alternative approaches to labor-supply modeling. The first review assesses the difference in-differences approach and its relationship to natural experiments. The second analyzes estimation with non-linear budget constraints and welfare-program participation. The third appraises developments of family labor-supply models including both the standard unitary and collective labor-supply formulations. The fourth briefly explores dynamic extensions of the labor supply model, characterizing how participation decisions, learning-by-doing, human capital accumulation and habit formation affect the analysis of the lifecycle model. At the end of each of the four broad reviews, we summarize a selection of the recent empirical findings. The concluding section asks whether the developments reviewed in this chapter place us in a better position to answer the policy-reform questions and to interpret the trends in participation and hours with which we began this review. q1999 Elsevier Science B.V. All rights reserved.
Keywords: J21; J22; J24; C21; C24; 330